Coeficiente de digestibilidade de farinha de insetos na alimentação de alevinos de tilápia do nilo (Oreochromis niloticus) - Fontes, Táfanie Valácio (2018)
The continuous increase of human population as well as animal production raised the use of products in diets formulations. That fact increased the demand and competition for protein sources between human and animal nutrition. Thus, to find out alternative protein ingredients is necessary. Taking this in consideration, insect meal becomes a very promising alternative protein source. The objective of this study was to determine the apparent digestibility coefficients (ADC) of five insect meals for Nile tilapia fingerlings. The experiment was carried out in the Fish Farming Sector of the Department of Animal Science of UFLA. A total of 900 fry, weighing 3g, were randomly distributed in 18 tanks with 250L in a completely randomized design with 6 treatments (control and Cinerea cockroach, Madagascar cockroach, Zophobas morio, Tenebrio molitor and Cricket meals) and 3 replicates. Determination of the apparent digestibility was performed using the indirect method, with chromium oxide (Cr2O3) as inert marker. After acclimatization period, animals were fed twice daily for 15 days. Feces were collected through Guelph modified method. It was observed higher dry matter ADC for Tenebrio molitor meal however not different from Zophobas morio meal (p < 0.05). The ADC of protein was higher for Tenebrio molitor and lower for Cricket meal, where other treatments did not differ among themselves (p < 0.05). For corrected protein, a higher ADC value was observed for Zophobas morio (81.19%) and Tenebrio molitor (88.68%) and lower for Cricket (p < 0.05). There were no differences between the treatments for ether extract digestion (p > 0.05), but when corrected for ether extract per unit in the diet, the highest ADC was observed for Madagascar cockroach and the lowest for Cinerea cockroach and Zophobas morio For chitin, a higher CDA was observed for Common Tenebrio meal and lower for Madagascar cockroach and Cinerea cockroach meal which shown the lowest value of ADC among all the treatments (p < 0.05). For ash, high ADC was obtained for Tenebrio molitor, Cinerea cockroach and Madagascar cockroach (p < 0.05). The ADC for Tenebrio molitor and Zophobas morio were the highest for energy while Cricket and Madagascar cockroach had the lower and Cinerea cockroach did not differ from the last two treatments (p < 0.05). In conclusion, the animals have a good usage of the five insect meals evaluated, where Tenebrio molitor and Zophobas morio have shown more promising.